Purification of Large Amounts of Murine Ribonucleic Acid Tumor Viruses Produced in Roller Bottle Cultures - Syrewicz, James J. (1972)
Murine ribonucleic acid tumor viruses and C-type virus particles are produced in relatively large quantities in roller bottle cultures. The viruses present in large volumes of culture fluids can be purified by a simple two-step procedure involving polyethylene glycol precipitation and equilibrium centrifugation in sucrose density gradients.